STUDI KEKUATAN LELAH TEKUK PADA BESI POROS ENGKOL 2 SILINDER UNTUK ENGINE RUSNAS 500 CC - Josowidagdo, Landjono (Industrial and Systems Engineering Assessment Journal (INASEA), 2005)
Nodular cast iron is increasingly being used in mass production of automotive engine crankshaft. A better understanding of characteristics of bending fatigue strength of the iron crankshaft is necessary to further the use of the material in this application. The research deals with Engine Rusnas 500 CC with iron crankshaft concerning the fatigue behaviors and influential factors.